2019
DOI: 10.15761/mhar.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction among Indian help-seeking patients with mental health disorders

Abstract: Internet addiction is a pernicious behavioural disorder that has received increasingly more interest as societies become more technological. This study addressed the current lack of data in the Indian context by examining problematic internet use among individuals receiving treatment for mental health disorders. In addition, it examined specific uses of the internet that have the potential to be problematic and impact on quality of life, namely social media use and online gaming, the reasons why people used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, past couple of years has seen an increased mark of problematic internet usage especially among adolescents & young adults. Studies in the Indian context have shown the prevalence of internet addiction to be 1.3% in the general population (Nisbin, 2019). The excessive use of internet has become a major concern & is heavily being studied in literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, past couple of years has seen an increased mark of problematic internet usage especially among adolescents & young adults. Studies in the Indian context have shown the prevalence of internet addiction to be 1.3% in the general population (Nisbin, 2019). The excessive use of internet has become a major concern & is heavily being studied in literature.…”
Section: Introductionmentioning
confidence: 99%